2022
DOI: 10.1097/j.pbj.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis in a young asymptomatic COVID-19 patient

Abstract: We report an unusual case of cerebral venous thrombosis (CVT temporally associated with an otherwise asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. While coronavirus disease 2019 (COVID-19) has been associated with thrombotic events at different sites, most published cases report on symptomatic SARS-CoV-2 infection. We are confident this was an otherwise asymptomatic infection as the patient reported no symptoms and molecular and serological testing was consistent with inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…16 The median time duration from COVID infection to CVT diagnosis reported is seven days (range 1–120 days). 9, 3539 The largest multicentric observational study published consisting of 20 patients also reported a male predominance (70%) and a mean age of 42.4 years at the time of presentation. 9 Traditionally, non-COVID-CVT is more common in young females (59%–75%), mostly in their second and third decades of life.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…16 The median time duration from COVID infection to CVT diagnosis reported is seven days (range 1–120 days). 9, 3539 The largest multicentric observational study published consisting of 20 patients also reported a male predominance (70%) and a mean age of 42.4 years at the time of presentation. 9 Traditionally, non-COVID-CVT is more common in young females (59%–75%), mostly in their second and third decades of life.…”
Section: Discussionmentioning
confidence: 98%
“…Among the published case reports, the majority of COVID-CVT cases are middle-aged to elderly males. Traditional CVT-related risk factors were absent 17,[28][29][30][31][32][33][34][35][36] except for two cases having OCPs 16,37 with one also being obese. 16 The median time duration from COVID infection to CVT diagnosis reported is seven days (range 1-120 days).…”
Section: Covid-cvtmentioning
confidence: 94%
“…Compared with other serious neurological events, CVST potentially associated with COVID-19 vaccination has the greatest amount of high-grade evidence ( Table 7 ). 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 Across 9 case reports detailing 23 cases, CVST was described mostly in patients 60 years and younger (20/23; 87%) and predominantly occurred in females (19/23; 782%). The most frequent presenting symptoms included headache, motor deficits, and myalgias.…”
Section: Cerebral Venous Sinus Thrombosismentioning
confidence: 99%